NON-WORKING TIME OF THE PRINCIPAL OF THE KYIV SCHOOL UNDER THE CONDITIONS OF MARTIAL LAW - Kostiantyn Lynov; Diana Sabol (Неперервна професійна освіта: теорія та практика)
The article was written based on the results of a study that was conducted in January-February 2024 among the directors of two capital districts – Solomyanskyi and Desnyanskyi. The goal was to find out the level of resource status of the head of the school in his free time from work in the conditions of martial law. Does he have the opportunity to maintain a balance between workload and rest so that there is enough resource for work? Does the director deal with burnout prevention? These questions are the subject of research. The priority for the head of a capital school under martial law is work, his professional activity. At the same time, he is faced with significant, first of all, psychological burdens, but does not pay enough attention to those measures aimed at restoring the personality and its energy potential. Two-thirds of respondents feel that they have a low level of energy for life after the working day, and almost 15% of them record a state of exhaustion. A third of the respondents have signs of burnout. The answers of the respondents indicate that the problem of resource recovery and accumulation is perceived by school leaders as a necessary solution. During the period of martial law, it is more important for the head of the school to take care of his mental health, prevention of burnout, acquisition of vitality, and resource conservation than during a normal period of peace. From the managerial point of view, there is a need to return to the normalization of working hours for educators, redistribution of powers within the school team, based on real autonomy (primarily organizational) recorded in domestic legislation.